Pengaruh Faktor Makro Ekonomi Terhadap Indeks Harga Saham Sektoral di Bursa Efek Indonesia (Data Bulanan Periode 2007-2014) - Mardiana, Lely Fitri (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to investigate the relationship between macroeconomic factors and sectoral indices on Indonesia Stock Exchange. This study use monthly data of sectoral indices return using Seemingly Unrelated Regression analysis withÂ  multifactor model. The results showed that macroeconomic factors give different effect to sectoral indices. Because of the characteristics, each sector respond differently to macroeconomic conditions in Indonesia. Monetary macroeconomic factors (BI Rate, inflation, exchange rate) negatively effect basic industry and chemical, consumer goods, manufacture, mining, miscellaneous industry, and trade sector. Real macroeconomic factors (foreign exchange reserves, exports, Indonesia crude oil prices) negatively effect agriculture, infrastructure, manufacture, mining and miscellaneous industry sector. Economic crisis condition in 2008 negatively affect all sectors. Keywords: Macroeconomic, Sectoral Indices, Â Seemingly Unrelated Regresssion